Longitudinal study of cognitive changes in MS – dimensionality, predictors and self-perception of change - Dirvanskiene, Ramune (The University of Edinburgh, 2016)
Background: Multiple sclerosis (MS) is a neurological disorder and the most frequent neurological cause of disability in young adults. 40-65% of MS patients experience cognitive difficulties (Bennedict et al., 2012), with problems in memory, attention and information processing speed being most frequently reported. However, visuoperceptual and language functions are much less studied in MS, but the few studies that looked into them (Vleugels, 2001; Grossman, 1995) have found prevalence of significant posterior deficits in MS. Up to today no study has investigated the domain-specificity of cognitive dysfunction in MS and its longitudinal progression. Aims: The primary aim of this project was to investigate the dimensionality of MS-related cognitive impairment longitudinally. The second aim was to determine the predictors of the observed longitudinal changes. The third aim was to investigate whether the participants themselves were aware of their cognitive changes, and what predicted the self-perception of change. Methods: To address these aims I followed a sample of MS patients and compared their performance on cognitive tests measuring five cognitive domains (verbal memory, visuospatial memory, processing speed, visuoperceptual and language) at baseline and at follow-up three years apart. Then I’ve composed separate models to explain the predictors first of the actual changes, and then of the perceived changes in performance. Moreover, as part of this project I have analysed pre-existing data to evaluate the instruments and optimized the baseline test battery for use in performing the followup assessments. Findings: I have managed to collect follow-up data on 82 MS patients and 23 matching healthy controls, acquiring high (76% and 79% respectively) recruitment rates. My MS sample (24% PPMS, 34% SPMS and 46% RRMS) was representable of the overall MS population. I found that deficits were seen in all cognitive domains (none were spared) and that new deficits were picked up sporadically, although with higher predisposition towards the information processing speed, visuoperceptual and memory domains. The new deficits showed the tendency to slowly accumulate, leading to development of major problems with longer disease duration. Interestingly it was found that even though the factors that influenced cognitive decline were specific for each of the cognitive domains, however, neurological disability, MS type and levels of depression were the most common predictors of change in cognitive functioning. I found that in general MS patients perceived longitudinal changes on the BRBN battery more accurately than on visuoperceptual and language tests, and the factors that played a role in the self-perception of change were executive dysfunction, neurological disability and MS impact. Implications: The results of this study add significant contribution to the field of longitudinal change in cognition in MS. Not only I explored the dimensionality of MS-related cognitive deficits, but also examined the factors that led to poorer performance, and the patients’ own perspective of their cognitive change. Moreover, with this project I have addressed common problems in the field of longitudinal research in MS – definition of normal variation in performance; the sensitivity of cognitive tests to pick up MS-related deficits; and heterogeneity of cognitive impairments in MS; - and I have used the performance of my own controls in attempts to account for all of that. I believe that this study will be of interest not only to those who specialize in cognitive functioning in MS, but also to those who question the methods employed in clinical research to define impairments and to account for individual differences.
Keywords: Multiple Sclerosis; cognition; longitudinal; predictors; insight